Burnt alive - Mangalwadi, Vishnal (Mumbai, India : GLS Publishing, 1999)
An account of the killings of Graham Stewart Staines and his two sons in Orissa, India and the media coverage thereafter; also highlighted is the current persecution against Christians in India.
Subtitle oncover: The Staines and the God they loved: missionaries murdered in Manoharpur.
Brethren missionaries.
Keywords: Staines, Graham Stewart, -- 1941-1999; Mayurbhanj Leprosy Mission; Brethren movement -- Missionaries -- India -- Biography; Missionaries -- India -- Orissa; Persecution of Christians -- India